Tooth bending stress and tooth impact stress of thin-rimmed spur gear - Ismail Ali, Abdul Aziz (2022)
The main advantages of the thin-rimmed spur gear are its reduction in gear's weight and the wide usage in various application. The efficiency of an engine can be improved by possessing a lightweight and efficient gear system. Thus, the use of thin-rimmed gears is prevalent in most applications involving gear usage. This study aimed to evaluate the effects of rim thickness, web thickness, and web arrangements, on tooth bending strength of thin-rimmed spur gears using the Finite Element Method; and to analyse impact energy, impact strength on tooth toughness, and tooth displacement of thin-rimmed spur gears using an impact test rig. The basic American Gear Manufacturers Association (AGMA) equation was utilised in this investigation to forecast gear tooth root stresses, which were then compared to finite element analysis. For further analysis, sets of thin-rimmed spur gear with various rim and web thicknesses were simulated in Abaqus 6.14 software as a finite element (FE) model. The FEA was based on symmetric and asymmetric web arrangements. von Mises stress values were extracted at Hofer's critical section on the tensile side of the second tooth in contact. Resultantly, the root stress values increased constantly upon reducing the applied rim thickness. The FEA results revealed the maximum von Mises Stress at the middle of Hofer's critical section of the solid spur gear. Both type of web arrangements has higher maximum von Mises stress compared to solid model. As comparison, asymmetric model was 13% higher compared to symmetric model at the highest von Mises stress increment ratio. To achieve the second objective, an impact test mechanism was developed to determine the tooth impact strength on the thin-rimmed spur gear tooth. A data logger used to obtain strain readings on a strain gauge installed at Hofer's critical section on a single gear tooth tested. A positive relationship detected between the height of load drop and impact energy values. Data from the impact test experiment revealed the span measurement achieved largest displacement as a higher load applied to the gear tooth. As comparison, asymmetric part TA4 was 5% higher compared to symmetric part TS4 at the largest displacement. Part TA4 and TS4 hit the largest displacement value as both have the thinnest rim and web thickness. Conclusively, asymmetric web arrangement has a higher tooth root stress value and a largest displacement of span measurement compared to symmetric web arrangement.